A Drag Queen in Your Living Room: Michael Cunningham’s Revision of Assimilative Gay Fiction (American & British Studies Annual, 2008)
The paper explores Michael Cunningham’s revision of the concept of assimilative gay fiction in his novel Flesh and Blood (1995). Unlike other authors of this stream of gay fiction, who avoid the central elements of American gay culture in their novels, Cunningham brings the themes of AIDS, camp, and drag queens into the literary mainstream and in this way performs a revision of the very concept of assimilative fiction.
Keywords: American gay fiction; homosexuality; assimilative gay fiction; Michael Cunningham; Flesh and Blood; AIDS; drag queens